2022
DOI: 10.3390/antibiotics11050605
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid Nano-Micelles versus Alcohol-Based Hand Sanitizer: A Comparative Study for Antibacterial Activity against Hospital-Acquired Infections and Toxicity Concerns

Abstract: Hospital-acquired infections (HAIs) are considered to be a major global healthcare challenge, in large part because of the development of microbial resistance to currently approved antimicrobial drugs. HAIs are frequently preventable through infection prevention and control measures, with hand hygiene as a key activity. Improving hand hygiene was reported to reduce the transmission of healthcare-associated pathogens and HAIs. Alcohol-based hand sanitizers are commonly used due to their rapid action and broad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 110 publications
2
32
0
Order By: Relevance
“…In addition, an in-vitro study confirmed the superior safety of rhamnolipids nano-micelles against human dermal fibroblast cells over alcohol-based hand sanitizer [ 23 ]. Thus, we previously recommended rhamnolipids nano-micelles to replace alcohol-based hand sanitizer for hand sanitization [ 23 ].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, an in-vitro study confirmed the superior safety of rhamnolipids nano-micelles against human dermal fibroblast cells over alcohol-based hand sanitizer [ 23 ]. Thus, we previously recommended rhamnolipids nano-micelles to replace alcohol-based hand sanitizer for hand sanitization [ 23 ].…”
Section: Introductionmentioning
confidence: 95%
“…Rhamnolipids are biosurfactants produced by Pseudomonas aeruginosa and could be produced efficiently and economically at industrial scale [ 20 , 21 , 22 ]. We previously reported the antibacterial activity of rhamnolipids nano-micelles against selected resistant Gram-negative and Gram-positive bacteria, and a docking study showed rhamnolipids nano-micelles to be effective against SARS-CoV-2 [ 6 , 23 ]. In addition, an in-vitro study confirmed the superior safety of rhamnolipids nano-micelles against human dermal fibroblast cells over alcohol-based hand sanitizer [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, finding a selective delivery system that could deliver antibiotics to the infected sites while decreasing or avoiding their accumulation at off-target tissues and being able to overcome efflux-mediated resistance mechanisms could result in a dramatic improvement of the antibacterial activity of antibiotics. Nanoparticles (NPs) are an advanced delivery system, and interest in their clinical development for different diseases, including combating infections, has been growing over the last few years [ 4 , 7 , 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. This is mainly attributed to their unique physicochemical properties, such as small particle size ranging from 1 to 1000 nm and a high surface area [ 32 ], being able to control/sustain drug release [ 33 , 34 ], deliver the antibiotics selectively at high concentrations into the infected sites, and thus, there is less possibility of bacteria developing resistance [ 15 , 35 , 36 ]; moreover, a lower possibility of drug accumulation at off-target sites [ 14 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This made nanomedicines to be able to overcome the limitations of conventional therapy 24 such as high frequency of drug administration 20 improve the delivery of a hydrophilic drug into cells 25 improve the bioavailability of poorly soluble drugs, control/sustain drug release 26,27 and aid crossing the blood-brain barrier 28,29 . Nanoparticles (NPs) have been applied previously for diagnosis, prevention, and treatment of several diseases such as viral infections with promising results 27,[30][31][32][33] , and and also, they demonstrated a good antibacterial activity against multidrug resistant bacteria, 17,[34][35][36][37][38][39] and for treatment of cancer, Alzheimer's, tuberculosis, wound healing repairing damaged tissue [40][41][42] , and inflammation 43 .…”
Section: Introductionmentioning
confidence: 99%